2016
DOI: 10.5455/ijmsph.2016.07012016381
|View full text |Cite
|
Sign up to set email alerts
|

Study of hematological and biochemical changes in dengue fever at tertiary care hospital at Ahmedabad

Abstract: Background: Dengue viral infections are the most important mosquito-borne diseases of the Indian subcontinent and have become a major global public concern. Objective: To evaluate hematological changes in serologically proven patients with clinical manifestations of dengue fever at tertiary care hospital. Materials and Methods: Cases of fever, clinically suspected to be dengue were confirmed by immunochromatographic tests for dengue NS1 antigen and dengue IgM antibody during the period from September 2015 to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
7
6
0
Order By: Relevance
“…3,19 In the present study, most were between 12-25 years, the average age was 32 years, with a slight male preponderance similar to others probably due to occupational exposure and increased recreational activity in men. 1,10,11 An analysis of hematology tests showed leucopenia in 36% of cases in the present study in concordance with others. 5,9 Few studies showed higher proportion and lower proportion of cases with leucopenia.…”
Section: Discussionsupporting
confidence: 92%
“…3,19 In the present study, most were between 12-25 years, the average age was 32 years, with a slight male preponderance similar to others probably due to occupational exposure and increased recreational activity in men. 1,10,11 An analysis of hematology tests showed leucopenia in 36% of cases in the present study in concordance with others. 5,9 Few studies showed higher proportion and lower proportion of cases with leucopenia.…”
Section: Discussionsupporting
confidence: 92%
“…23,24 A few studies had a lower and others, a higher proportion of cases with leucopenia. 1,2,4,15,16,18,25 A normal leucocyte count was observed in 55% of cases in our study in concordance with few studies but it was lower and higher in other studies. 2,4,15,18,21,24 Leucocytosis was noted in 9% of cases in our study in concordance with few studies.…”
Section: Discussionsupporting
confidence: 91%
“…1 The clinical manifestations include headache, fever, retro orbital pain, myalgia, body pain, rash.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Singh R study [15] is similar to present study. The result of Patel PM study [14] and Singh R study [15] are similar to that of the present study.…”
Section: In Study Of Dengue Fever Male-to-female Ratio In Different Ssupporting
confidence: 90%